Estimation of the influence of natural rubber industry in Malaysia: special reference to China / Khairul Bariah Hamidi - Hamidi, Khairul Bariah (Faculty of Plantation and Agrotechnology, 2018)
Natural rubber (NR) on the market has small increase in demand but big increase in supply. This study is conducted to analyze factor affecting the demand of natural rubber in Malaysia and the short run and long run relationship between the variables. This study is focus on the export of Malaysia’s rubber to China as the proxy to the demand of natural rubber. This is because, China is the largest importers of rubber from Malaysia. Monthly data from 2013 until 2017 are obtained from Malaysia Rubber Board, Central Bank of Malaysia and Department of Statistic Malaysia. The data were tested for VECM model. Results of unit root test revealed that export of natural rubber is stationary at level and natural rubber price, exchange, synthetic rubber price and crude oil price is stationary at the first difference. The co-integrating test also indicates that there is a co-integrating between the variables. All the variables have a significant effect on the export of natural rubber in the long run at 5% level while only crude oil price and natural rubber price influence the export of natural rubber in the short run at 5% level and 1% level. Thus, it can be concluded that this study can help the government to plan the policies to stabilize the rubber industry in Malaysia.